Perlindungan Hukum Internasional Terhadap Anak Luar Kawin Pekerja Migran Indonesia (Analisis Kritis Penerapan Prinsip Non-Diskriminasi) - Mardiyanto, Ibnu (PROGRESIF: Jurnal Hukum, 2024)
Extramarital children of Indonesian migrant workers face complex issues of identity and citizenship rights. In Indonesia, extramarital children often do not have birth certificates, which makes it difficult for them to access public services such as schools. The principle of non-discrimination is the most important in legal protection for extramarital children. The rights of children are recognized internationally in the Convention on the Rights of the Child, where the protection of the rights of extramarital children includes the protection of the juridical rights of extramarital children to demand recognition and validation, as well as the management of the citizenship status of the Republic of Indonesia for the child. The following results show that First, the application of the principle of non-discrimination is specifically recognized in the Convention on the Rights of the Child, which underlines the rights of children in the absence of discrimination based on the marital status of their parents and requires States Parties not to discriminate against them. Second, the implementation of children's rights, especially the rights of extramarital children of Indonesian migrant workers in various regulations in Indonesia, needs to be maintained consistently, involving aspects of substance, structure, and cultural values, so that they can provide tangible benefits and are based on a deep sense of justice. Keywords: protection of international law; extramarital child; non-discrimination